Mechanism of micronuclei formation in polyploidizated cells of Allium cepa exposed to trifluralin herbicide - Fernandes, Thais C. C.; Mazzeo, Dania Elisa C.; Marin-Morales, Maria A. (Elsevier B.V., 2007)
The trifluralin is an agent that promotes a cellular damage due to its direct action on the microtubules. This action leads to a decontrol in the cellular division, bringing about polyploid cells. In this work, we show the evidences that the exceeding genetical material of theses polyploidizated cells tends to be eliminated from the nucleus in the form of micronucleus. Our analyses prove this fact, both by the presence of a number of cells carrying micronucleus, and by the evidences of the elimination of the exceeding material itself, after exposition of the Allium cepa root tips tested with several concentration of trifluralin herbicide. It was noticed that the residual concentration induced a number of polyploid cells, micronuclei and mini cells. Inferences about the implications of the elimination of genetic material from micronuclei, such as cell viability and apoptosis, are also presented. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: trifluralin; Allium cepa; micronucleus; nuclear buds; mini cells; aneugenic agent; polyploid cell; mutagenicity; dinitroanilines; chromosome losses